Numerical Study of Radiative and Dissipative MHD Casson Nanofluid Over a Cone With High‐Order Chemical Reaction - Sademaki, L. Joseph; Reddy, B. Prabhakar; Matao, P. M. (Engineering reports (Hoboken, N.J.), 2025)
ABSTRACT This study investigated the dissipative effects on time‐dependent Casson nanofluid motion over a cone, considering variable heat source/absorption and higher‐order reacting species. Water ethylene glycol was employed as the Casson base fluid. The dimensional PDEs were transformed into dimensionless PDEs by fitting non‐dimensional parameters and solved using an effectual Galerkin finite element method (GFEM). The impact of physical parameters on momentum, energy, and concentration profiles is analyzed via graphical representations. The wall friction, thermal, and solutal transport rates are tabularly detailed. It was detected that increasing the absorbency parameter, Eckert number, thermal radiation, and thermal generation improves fluid velocity. Conversely, intensifying the magnetic field, Prandtl number and inclination angle reduces fluid velocity. The nanofluid temperature declines with a mounted Prandtl number and nanoparticle volume fraction, and the opposite effect is perceived with increased Eckert, Dufour, and Soret numbers. Wall friction intensifies with rising porosity, magnetic field strength, Casson parameter, and diffusive parameters, while it diminishes with higher nanoparticle volume fraction. The findings distinctly indicate that Ag−WEG$$ Ag- WEG $$ nanofluid exhibits superior effectiveness in enhancing thermal and mass exchanges compared to Al2O3−WEG$$ Al_2O_3- WEG $$ nanofluid. Furthermore, a comparative analysis agrees with earlier findings. This current model problem finds application across various scientific, engineering, and technological domains, including energy production, space exploration, food preservation, agricultural product manufacturing, materials processing, astrophysical phenomena, biomedical procedures, and enhanced oil recovery. This study investigated the dissipative effects on time‐dependent Casson nanofluid motion over a cone, considering variable heat source/absorption and higher‐order reacting species. Water ethylene glycol was employed as the Casson base fluid. The proposed model has broad applicability across various scientific, engineering, and technological domains.